Teacher’s Gender-Biased Attitude on Female Students Performances in Science Subjects in Secondary Schools in the Kumba Municipality - Fobellah, Efuetngwa Diana (American Journal of Education and Practice, 2024)
Purpose: The purpose of this study is to examine the influence of teachers gender-biased attitude on female students performance in science subjects. Materials and Methods: It was a survey study using three sets of questionnaire, Data were obtained form 172 parents, 298 students and 79 science teachers in Kumba Municipality. Descriptive and inferential statistical techniques were applied to obtain percentages, bar charts, means, standard deviation, x2 – and Z- values. Findings: The data analysis showed that teachers attitudes towards the female students tend to affect these students’ achievements in science subjects. More of the female students (38 out of 49) who said teachers had positive attitudes passed than those who said teachers attitudes were negative (7 out of 97). Implications to Theory, Practice and Policy: Based on the results, the researcher recommends that; Teachers should be aware of the differences boys and girls bring to the learning of science, girls should be encouraged to observe female role models in science careers and strive to be like them.